Advising New Students with Disabilities - MaryBeth Walpole; Jay Chaskes (Journal of College Orientation, Transition, and Retention, 2011)
This study focuses on students with disabilities' (SWD) transition to and experiences in college using both quantitative and qualitative data. SWD report similar levels of interaction with advisors and faculty, despite the additional contact that accommodations typically require. SWD also persist at lower rates than do their non-disabled peers. On campuses, SWD must contend with decisions about disclosure, seeking accomodations, self-advocacy, college bureaucracy, and time management. Recommendations are to include disabilities as one aspect of campus diversity within orientation programming and created orientation programs specifically designed for SWD and their parents.